Mapping type III intragranular residual stress distributions in deformed copper polycrystals - Jiang, J; Britton, T; Wilkinson, A (2013)
Cross-correlation-based analysis of electron backscatter diffraction patterns has been used to map the intragranular residual stress variations in polycrystalline copper samples deformed to different plastic strain levels of 0%, 2%, 6% and 10%. We map the deviation from the mean stress within each grain and present histograms of stress levels mapped over many grains which show a central Gaussian-like peak with non-Gaussian tails at the higher stress magnitudes. The width of the peaks increased with increasing plastic deformation and the tails became more obvious. Plots correlating maximum in-plane shear stress and distance to the nearest grain boundary demonstrate that stress "hot spots" tend to accumulate near grain boundaries. © 2013 Acta Materialia Inc.